Legal risks of owning cryptocurrencies - LOW, Kelvin F. K. (Institutional Knowledge at Singapore Management University, 2017)
Cryptocurrencies like Bitcoin have matured from being associated exclusively with techies and radicals to being considered by central banks as a technology to implement digital money. Cryptocurrencies exist only in digital form and can be transferred completely between digital addresses. This is both unlike conventional electronic money as understood by laypersons which acts as a debt claim on a deposit with a trusted financial institution such as a private bank and unlike conventional corporeal money which may be physically possessed. This means that any legal rights associated with holding cryptocurrencies must be different despite it being remaining open to interpretation. In this chapter, we look at the various treatments of money in the legal sense and discuss the risks associated with each by drawing on real life examples. We conclude that fraud through hacking could potentially pose a problem to widespread adoption of cryptocurrencies as the absence of recourse against a third party such as a bank concentrates risk in holders of cryptocurrencies. Users should thus exercise caution and understand the risks before investing in cryptocurrencies. This warning requires emphasis as many parties misapprehend the cryptography within the technology as protecting them from such fraud when in fact it does no such thing. We discuss the various legal treatments of both non-digital and digital money before crytocurrencies came about. This is followed by an introduction to Bitcoin/cryptocurrencies and how they work differently from money as we know it. We then look at the legal risks associated with cryptocurrencies and associate them with some real-life examples.